Transmission of External Shocks in Assessing Debt Sustainability, the Case of Macedonia - Danica Unevska Andonova; Dijana Janevska Stefanova (National Bank of the Republic of Macedonia, 2015)
In the analysis of public and external debt sustainability the National Bank of the Republic of Macedonia is actively using the IMF's Debt Sustainability Analysis (DSA) framework. The aim of our analysis is to improve the analytical power of the IMF's DSA framework, in the case of Macedonia. This paper uses simple framework, based on methodology used in Adler and Sosa (2013), that integrates econometric estimates of the effect of global factors on key domestic variables that determine public and external debt dynamics, within the IMF's standard debt sustainability framework. VAR estimation is used in obtaining the forecasts of key domestic variables, conditional on a set of assumed global variables under different global shock scenarios. The results in general suggest that under all shock scenarios, there is negative effect to domestic GDP, however in the case of current account there is negative effect in the beginning of the period of applied shocks, but positive in the later period. Consequently, the expected effect to public debt sustainability is negative for the whole period due to lower real GDP growth. However, regarding external debt sustainability, negative effect is expected in the first year or two due to lower GDP growth and higher current account deficit, yet, in a medium run, external sustainability might not be jeopardized as the lower GDP growth might be neutralized by the lower current account deficit.
Keywords: C32; E60; F42; F47; 330; public debt; external debt; debt sustainability; Macedonia